Kajian Paket Dosis Semi Organik terhadap Sifat Tanah dan Hasil Tanaman Padi (Oryza sativa L) - I WAYAN NARKA; I NYOMAN DIBIA; I WAYAN DANA ATMAJA (Fakultas Pertanian Universitas Udayana, 2020)
The study of packages of semi-organic fertilization on soil properties, and yield of rice (Oryza sativa L). The aim of this study was to know the effect of semi organic fertilization doses on soil properties and yield of rice. The Randomized block design (RBD), with 3 replications and 9 treatments was used in this study. P0 (without fertilizer), P1 (25 tons of organic fertilizer ha-1), P2 (300 kg of Urea ha-1, 150 kg SP36 ha-1 and 75 kg KCl ha-1), P3 (biourin liquid fertilizer) P4 (½ P1 + ½ P2), P5 (½ P1 + ½ P3, P6 (½ P2 + ½ P3), P7 (2/3P1 + 1/ 3 P2) and P8 (2/3P3 + 1/3P2). The results showed that the application of semi-organic fertilizer on soil properties such as soil salinity, C-organic content, P-available and Nitrogen content of soil significantly affected by the treatment, while potasium_available and soil pH is not significantly affected by the treatment. Yield of rice had a very significant effected by treatment. The semi-organic fertilizer P4 (combination of 50 % anorganic + 50 % organic compost) and P6 (combination of 50 % inorganic + 50 % biourine) can produce oven dry grain 33.35 g per bushel and 32.63 g per bushel respectively or increased 57.91 % and 54.50 % of controls.